N2 Fixation in the Eastern Arabian Sea: Probable Role of Heterotrophic Diazotrophs - Kumar, P. Kiran; Singh, Arvind; Ramesh, R.; Nallathambi, T. (Frontiers in Marine Science, 2017)
Biogeochemical implications of global imbalance between the rates of marine dinitrogen (N2) fixation and denitrification have spurred us to understand the former process in the Arabian Sea, which contributes considerably to the global nitrogen budget. Heterotrophic bacteria have gained recent appreciation for their major role in marine N budget by fixing a significant amount of N2. Accordingly, we hypothesize a probable role of heterotrophic diazotrophs from the 15N2 enriched isotope labelling dark incubations that witnessed rates comparable to the light incubations in the eastern Arabian Sea during spring 2010. Maximum areal rates (8 mmol N m-2 d-1) were the highest ever observed anywhere in world oceans. Our results suggest that the eastern Arabian Sea gains ~92% of its new nitrogen through N2 fixation. Our results are consistent with the observations made in the same region in preceding year, i.e., during the spring of 2009.